Minutes of Finance and General Purposes Committee (extract)
017a-0011-001 MINUTE OF FINANCE AND GENERAL PURPOSES COMMITTEE, 21ST NOVEMBER, 1938. 16. VISIT OF BRITISH WOMEN TO SPAIN. With regard to the letter which had been referred to the Finance and General Purposes Committee by the General Council from the Committee of Liason of the Local Federation of Barcelona, C.N.T., U.G.T., inviting the General Council to appoint a women's delegation to Spain, it was reported that the International Federation of Trade Unions had been in communication with the U.G.T. who had written that when it was a matter of inviting organisations which were within the International Federation of Trade Unions all particulars in the matter of invitation should rest with the national Trade Union centre. IT WAS AGREED that no further action be taken. 292/946/17a/11